Comparison of Clinical Outcomes Between Autologous Cryosurgery Reconstruction and Bone Cement Reconstruction in Osteosarcoma - Irvan; Andriandi; Aga Shahri Putera Ketaren (Universitas Muhammadiyah Palu, 2026)
Background: Osteosarcoma is a primary malignant bone tumor that commonly affects adolescents and young adults. Limb-salvage surgery has become a preferred approach over amputation, with various reconstruction techniques such as autologous cryosurgery and bone cement reconstruction. However, the comparative clinical outcomes of these methods remain a subject of ongoing investigation. Objective: This study aims to compare the clinical outcomes between autologous cryosurgery reconstruction and bone cement reconstruction in osteosarcoma patients. Methods: A retrospective cohort study with a post-test only control group design was conducted using medical records of osteosarcoma patients treated at H. Adam Malik Hospital, Medan, from January 2022 to December 2025. A total of 22 patients were included and divided into two groups: cryosurgery (n=11) and bone cement reconstruction (n=11). Clinical outcomes were evaluated using MSTS scores, relapse rates, and metastasis incidence. Statistical analysis was performed using appropriate comparative tests with a significance level of p<0.05. Results: The results showed no statistically significant differences between the two groups in terms of MSTS scores (p=0.51), relapse rates (p=0.06), and metastasis incidence (p=0.64). Although the bone cement group demonstrated slightly higher MSTS scores, the difference was not significant. Similarly, relapse and metastasis rates were comparable between groups. Conclusion: Autologous cryosurgery and bone cement reconstruction provide comparable functional and oncological outcomes in osteosarcoma patients undergoing limb-salvage surgery. Both methods can be considered viable reconstruction options, with selection tailored to patient condition, resource availability, and clinical considerations. Further studies with larger sample sizes and prospective designs are recommended.